2010
DOI: 10.1017/s1751731110000881
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary l-arginine supplementation to gilts during early gestation on foetal survival, growth and myofiber formation

Abstract: The effects of L-arginine on porcine foetal development and myogenesis were determined. Twenty Swiss Large White gilts were randomly allocated to either the control (C) or L-arginine treatment (A). In addition to the standard gestation diet, A-sows received 26 g L-arginine daily from days 14 to 28 of gestation. At day 75 of pregnancy, sows were sacrificed and the number and weight of foetuses were recorded. From each litter, the lightest, heaviest and the ones with an average foetal weight (FtW) were selected.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
56
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(62 citation statements)
references
References 30 publications
5
56
1
Order By: Relevance
“…These results are partially in agreement with the positive effect of Arg supplementation on prolificacy obtained in sows (1% Arg; +2 piglets; Mateo et al, 2007;0.8% Arg;+3.7 piglets;Berard and Bee, 2010) and rats (1.3% Arg; +3 rats; Zeng et al, 2008). In rats Arg supplementation increased the number of implantation sites and the litter size at birth, but in pigs these authors did not found any effect on the total number of piglets born per litter, but a great effect on the piglet survival rate at birth, effect that was not observed in this study.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…These results are partially in agreement with the positive effect of Arg supplementation on prolificacy obtained in sows (1% Arg; +2 piglets; Mateo et al, 2007;0.8% Arg;+3.7 piglets;Berard and Bee, 2010) and rats (1.3% Arg; +3 rats; Zeng et al, 2008). In rats Arg supplementation increased the number of implantation sites and the litter size at birth, but in pigs these authors did not found any effect on the total number of piglets born per litter, but a great effect on the piglet survival rate at birth, effect that was not observed in this study.…”
Section: Discussionsupporting
confidence: 88%
“…There is no previous information about this lack of synergism between Arg and Gin on reproductive traits, although the single supplementation of these amino acids seem to exert different effects on the blood concentration of the other one. The single supplementation of Arg decreased the plasmatic Gin concentration in pregnant gilts (Mateo et al, 2007;Berard and Bee, 2010), whereas the single Gin supplementation increased the plasmatic Arg concentration (Wu et al, 2011). In pregnant rats, the single supplementation of Arg, exerted the opposite effect, and increased the serum Gin concentration (Zeng et al, 2008).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Dietary 1% L-arginine-HCl supplementation could markedly increase the live-born piglets by 2 per litter . Daily supplementation of 26 g L-arginine to gilts from d14 to d28 of gestation enhanced fetal survival and positively affected the primary phase of myofiber formation (Bérard & Bee 2010). Besides, dietary arginine supplementation could decrease maternal abortion rate and neonatal mortality in mice with porcine circovirus type 2 infection (Ren et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Third, as compared with control gilts, dietary supplementation with 0.4 or 0.8% L-arginine between days 14 and 25 of gestation increased placental weights 21-34% and number of viable fetuses per litter by approximately 2 . Fourth, supplementation with 1% arginine between days 14 and 28 of gestation increased the number of fetuses per litter by 3.7 on day 70 of gestation in superovulated gilts (Bérard and Bee, 2010). Fifth, supplementing 1% arginine to gilts beginning on day 17 of gestation for 16 days increased the number of live-born piglets per litter by 1.2 (De Blasio et al, 2009).…”
Section: Argininementioning
confidence: 99%